The little republic masculinity and domestic authority in eighteenth-century Britain - Harvey, Karen, 1971- (Oxford : Oxford University Press, 2012)
This title reconstructs the distinctive relationship between the house and masculinity in the 18th century; adds a missing piece to the history of the home, uncovering the hopes and fears men had for their homes and families.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Households -- Great Britain -- History -- 18th century; Husbands -- Great Britain -- History -- 18th century; Masculinity -- Great Britain -- History -- 18th century